Análisis del sector de autopartes en el TLC Colombia-Estados Unidos (2018)
The free traffic of merchandise between nations is a policy that has been implemented at the global level, the power to take goods manufactured in a country and be able to sell it easily abroad, taking advantage of the competitive advantage of each country, this is what generates the TLC, reduce barriers to trade, remove cost overruns that generated the taxes they charge for the entry of goods into their territories, with the aim of regulating the internal consumption of its inhabitants and protecting the national industry.